THE IMPACT OF THE COVID-19 PANDEMIC ON GLOBAL FOOD SYSTEM RESILIENCE - Kubatko, Oleksandr; Merritt, Rowena; Duane, Sinead; Piven, Vladyslav (Mechanism of an economic regulation, 2023)
The COVID-19 pandemic has brought significant challenges to food systems worldwide, exposing vulnerabilities in the global supply chains and threatening food security. The purpose of the research was to investigate the impact of COVID-19 on food system resilience globally. The study found that COVID-19 has disrupted global food systems through a combination of factors, including trade restrictions, supply chain disruptions, and reduced access to markets and labor. These changes have resulted in increased food insecurity, particularly for vulnerable populations, including low-income households and those living in countries heavily dependent on food imports. It was revealed that just after the outbreak of COVID-19, the prices of most agricultural products generally remained stable due to some economic factors. It was emphasized that some consequences of COVID-19 (e.g., high inflation rate) became apparent only when the majority of restrictive lockdown measures were lifted. The study concluded that addressing the impacts of COVID-19 on food security requires a multi-faceted approach that involves improving the resilience of food systems, investing in social protection programs, and ensuring equitable access to food for all populations.